2018
DOI: 10.1155/2018/4798359
|View full text |Cite
|
Sign up to set email alerts
|

BCI and FES Based Therapy for Stroke Rehabilitation Using VR Facilities

Abstract: In recent years, the assistive technologies and stroke rehabilitation methods have been empowered by the use of virtual reality environments and the facilities offered by brain computer interface systems and functional electrical stimulators. In this paper, a therapy system for stroke rehabilitation based on these revolutionary techniques is presented. Using a virtual reality Oculus Rift device, the proposed system ushers the patient in a virtual scenario where a virtual therapist coordinates the exercises aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…As a result, patients receiving VR showed at least some improvement in balance, mobility, range of motion, and gait performance [1,2,[47][48][49][50][51][52][53][54][55][56]; however, the studies we reviewed included small sample sizes with considerable variability for the age, gender distribution, post-stroke duration, duration of intervention, frequency of intervention, duration of sessions, percentage of dropouts, and outcome measures. Only a few studies adopted a HMD for VR alongside stroke rehabilitation, showing that patients improved upper limb function (strength, precision of movement, and range of motion) with more minor compensatory trunk movements and flexion and extension of the hand and fingers [57][58][59][60]. Moreover, they found better functional recovery for gait and balance [36].…”
Section: Strokementioning
confidence: 99%
“…As a result, patients receiving VR showed at least some improvement in balance, mobility, range of motion, and gait performance [1,2,[47][48][49][50][51][52][53][54][55][56]; however, the studies we reviewed included small sample sizes with considerable variability for the age, gender distribution, post-stroke duration, duration of intervention, frequency of intervention, duration of sessions, percentage of dropouts, and outcome measures. Only a few studies adopted a HMD for VR alongside stroke rehabilitation, showing that patients improved upper limb function (strength, precision of movement, and range of motion) with more minor compensatory trunk movements and flexion and extension of the hand and fingers [57][58][59][60]. Moreover, they found better functional recovery for gait and balance [36].…”
Section: Strokementioning
confidence: 99%
“…The use of motor imagery in VR-BCI is a good example of how these two technologies can potentially be combined. Although a large part of the research combining these techniques has been in healthy participants (e.g., Ortner et al, 2012;Lupu et al, 2018;, or is still at proof-of-concept stage (Aamer et al, 2019), early clinical studies have shown promise for neurorehabilitation (Remsik et al, 2018;Cohen et al, 2019;Vourvopoulos et al, 2019). However, the spatiotemporal imprecision is currently a limiting factor.…”
Section: Future Developments In Therapeutic Vrmentioning
confidence: 99%
“…Disruption of 'social' or 'interpersonal' touch [Huisman, (2017), pp.397-399] is currently the focus of research related to the design of remote and prosthetic interfaces. Until quite recently, research and design has focussed on information processing or 'message passing' (Figure 1) of touch signals, using haptic and kinetic devices for touch experience such as pressure, movement, vibration, skin stretch and warmth; through thermal signals (Willemse, 2018), intimate sexually touching (Gomes and Wu, 2017;Solon, 2014, Kiiroo, https://www.kiiroo.com/), stroking a hand (Eichhorn et al, 2008) or an arm (Huisman et al, 2016), hand holding (Gooch and Watts, 2012), emotion transmitting (Bailenson et al, 2007), hugging (Rosella and Genz, 2006), brain computer interfaces (Lupu, 2018). Such research and design primarily focus on imitation of tactile qualities, efficiency, immediacy, categorisation, automatisation and user experience.…”
Section: Related Workmentioning
confidence: 99%